The Effects of Congregational Prayer Intensity and Moral Values Reinforcement on Students' Emotional Maturity - Zulfikar Zulfikar; Burhanuddin; Yanto; Muhammad Alfi Syahrin (PT. Education Research Center, 2026)
This study investigates the effects of congregational prayer intensity and moral values reinforcement on students' emotional maturity in Islamic secondary education. It addresses limited empirical evidence concerning the simultaneous contribution of religious habituation and moral education to adolescents' socio-emotional development. A quantitative survey design was employed involving 100 students of SMA Muhammadiyah Batam during the 2025/2026 academic year. Data were collected using a structured five-point Likert scale questionnaire measuring congregational prayer intensity, moral values reinforcement, and emotional maturity. Instrument validity and reliability were assessed using Pearson Product-Moment correlation and Cronbach's Alpha. Data analysis included descriptive statistics, classical assumption tests, and multiple linear regression using IBM SPSS Statistics version 26. The findings reveal that congregational prayer intensity has a significant positive effect on students' emotional maturity. Moral values reinforcement also demonstrates a significant positive effect and emerges as the strongest predictor. Simultaneously, both variables significantly influence emotional maturity, with an Adjusted R² of 0.587, indicating that 58.7% of its variance is explained by the model. These findings demonstrate that religious habituation and moral education function as complementary strategies for strengthening emotional regulation, responsibility, empathy, and social competence, supporting a holistic approach to students' socio-emotional development in Islamic education.